Isothermal thermal decomposition of the HMX-based PBX explosive JOL-1. Issue 1 (2nd January 2021) - Huang, Qiong; Liu, Xuwang; Xiao, Yiyi; Luo, Liqiong; Luo, Guan; Jin, Bo; Peng, Rufang; Chu, Shijin
ABSTRACT: Isothermal thermal decomposition method was used to study the thermal behavior of the HMX-based PBX explosive JOL-1. The gas pressure versus time curves of the isothermal decomposition of JOL-1 were obtained within the temperature range of 90°C to 130°C. Kinetic parameters such as activation energy and frequency factor for the thermal decomposition of JOL-1 were obtained using the Arrhenius equation and model-fitting method. The model-fitting method further proved that the isothermal decomposition of JOL-1 at 90°C, 100°C, 110°C, 120°C, and 130°C is consistent with the No. 8 mechanism function, namely, the anti-Jander equation, controlled by 3D diffusion. The storage life of JOL-1 was estimated by the Semenov equation and the extent of reaction reached 0.1–0.4%. Results showed that the effective storage life of JOL-1 at 25°C, 40°C, and 60°C are 68 years, 10 years, 1 year, respectively, when the extent of reaction reached 0.1%.